IDENTIFICATION OF INSECT PESTS ON RICE CROPS (ORYZA SATIVA) IN GUNUNG SARIK RICE FIELD - Fidela, Wita (Jurnal Sapta Agrica, 2024)
Indonesia is an agrarian country with agriculture as the highest livelihood for its population. The agricultural sector that is the main pillar in Indonesia's food supply is in terms of rice agriculture (Oryza sativa), especially as the global population continues to grow. However, a challenge that often lurks in efforts to increase rice production is the attack of insect pests. Insect pests result in significant crop losses and threaten food security. It is necessary to identify rice pest insects as an effort to extract information on the types of insects that harm agriculture. This study using qualitative descriptive methods aims to determine the types of insect pest species on agricultural land in Gunung Sarik Village as a consideration in proper pest control management, so as to improve the quality and quantity of rice crops in the agricultural land of Gunung Sarik Village. Based on the results of the observations, it was found that types of insect pests come from two different orders, namely hemiptera, which include leafhoppers, walang sangit, and black ants, and the order orthoptera or grasshoppers.